Some 3-thioxo/alkylthio-1,2,4-triazoles with a substituted thiourea moiety as possible antimycobacterials - KÜÇÜKGÜZEL, İLKAY; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (My University, 2001)
A series of novel N-alkyl/aryl-N'-[4-(4-alkyl/aryl-2,4-dihydro-3H-1,2,4-triazole-3-thione-5-yl)phenyl]thioureas 1-19 and three S-alkylated representatives of the former, N-alkyl/aryl-N'-[4-(3-aralkylthio-4-alkyl/aryl-4H-1,2,4-triazole-5-yl)phenyl]thioureas 20-22, were synthesized and tested for antimycobacterial activity against Mycobacterium tuberculosis H37Rv as well as Mycobacterium fortuitum ATCC 6841 which is a rapid growing opportunistic pathogen. Compounds 4 and 9-11 were found to possess the same MIC value with that of Tobramycin against M. fortuitum ATCC 6841 whereas 1-3 and 21 had positive response against M. tuberculosis H37Rv at varying degrees. Compound 21 was identified as the most potent derivative of the 1-22 series by an MIC value of 6.25 microg/mL and selectivity index of 1.6.
Keywords: Animals; Triazoles; Microbial Sensitivity Tests; Antitubercular Agents; Chlorocebus aethiops; Thiourea; Vero Cells; Mycobacterium tuberculosis; Mycobacterium fortuitum